Efektivitas Penerapan Sistem Informasi Rencana Umum Pengadaan Pada Badan Kepegawaian Daerah Provinsi Sumatera Selatan - Novansyah, Tio; Hakim, Arif Rahman; Sandy, Amiruddin (@-Publik: Jurnal Administrasi Publik, 2025)
The effectiveness of implementing the General Procurement Information System (SiRUP) at the Regional Personnel Agency of South Sumatra Province is evaluated in this study. SiRUP serves as a means to carry out bureaucratic reforms in the procurement of goods and services (PBJ) by utilizing information technology. This implementation is in line with the government's commitment to implement e-Government and achieve Good Corporate Governance (GCG) principles.Through the electronically-based SiRUP application, PBJ processes are claimed to be faster, more accurate, transparent, and accountable. The General Procurement Plan is prepared and established within the SiRUP application. It provides information to the general public as a form of procurement transparency and also informs potential providers in a timely manner, allowing them to participate and compete in meeting government needs. The procurement process begins with needs planning, followed by the Regional Personnel Agency developing and finalizing the General Procurement Plan, and publicly announcing it on the designated website. Theee objective of this researchoh is to assess and understand the extent of the effectiveness of implementing the General Procurement Information System at the Regional Personnel Agency of South Sumatra Province. Additionally, the researchho aims to determine the influenceoe of Good Governance on the performance of procurement of goods and services. The research methodology employed in this study is a quantitative descriptive method. Based on the data analysis, it is found that the implementation of the SiRUP application has a positive and significant impact on the performance of procurement of goods and services.